Strategi Koping Guru dalam Penanganan Siswa di Kelas Rendah Sekolah Luar Biasa - Riyanti, Rahayu Febri; Taufik, Taufik (Universitas Muhammadiyah Metro, 2023)
Teaching children with special needs in lower grades presents unique challenges that often lead to stress among educators. These children's behaviors frequently deviate from typical classroom conduct, and teachers may perceive them as inappropriate or disruptive. For instance, some students may shout for attention, which can be demanding for teachers already juggling the needs of multiple students. Special education teachers shoulder heavier responsibilities compared to their counterparts in regular schools. Notably, not all teachers possess the self-control required to manage negative behaviors during the teaching process. To navigate these stressful situations, educators employ coping strategies that depend on their individual coping resources. This study aimed to explore the coping strategies employed by lower-grade teachers in Special Schools, using qualitative methods. Nine teachers from Special Schools served as informants, and data were collected through interviews and observations, validated through triangulation, and analyzed following Miles and Huberman's interactive data analysis model. The research findings identified various stressors for Special School teachers in Surakarta, including challenging student behavior, difficulty understanding children with special needs, non-verbal and non-reading students, those not yet toilet-trained, parental demands, suboptimal classrooms, and inconsistent treatment. Teachers' coping strategies varied, encompassing positive thinking to address stress stemming from students' behavior and special needs comprehension, self-control for managing challenging behavior and parental demands, taking responsibility for addressing these stressors, planned problem-solving for behavioral and parental challenges, concrete problem-solving for specific issues, and seeking social support from family and colleagues to cope with overall stressors. In conclusion, teaching children with special needs in lower grades is a demanding task that can lead to stress for educators. However, this research sheds light on the coping strategies employed by these teachers, emphasizing the importance of a diverse toolkit to effectively manage the multifaceted challenges they face in Special Schools.